Old and new friendships of Latin American immigrants - de Oliveira, Mariana Sarro Pereira (Seven Editora, 2024)
In view of the growth of international migration, including in Latin America, the present investigation aimed to analyze the history of old and new friendships of Latin American immigrants throughout their lives in the new country (Brazil, other Latin American countries, Spain and Portugal). More specifically, it was intended to investigate how recent migration affects existing friendships and the formation of new ones, with people of any nationality and culture. 40 immigrants participated in this descriptive-qualitative study (70% women and 50% between 30 and 39 years old), divided into four groups: A) 20 Latin Americans who lived in Brazil; B) three Brazilians who lived in another Latin American country; C) 12 Brazilians who lived in Spain; and D) five Brazilians who lived in Portugal. The instrument used was a questionnaire with open questions, sent and received by e-mail, producing written reports. In total, direct contacts were made by e-mail with national and international universities and educational institutions, as well as by messages on social networks with approximately 1,000 people, between August 2014 and January 2016. A detailed analysis of the data was conducted with a coding process (interpretation of the statements), and subsequent organization of the material into categories, based on qualitative content analysis. The main results of the study pointed out that most of the close friends are of the same gender and of the same nationality, and most of them reside in the country of origin of the immigrant. The ties in the immigrant’s country of origin are close friendships, of many years, whose main means of contact are Facebook, Skype, WhatsApp, telephone, e-mail, internet and in person, and the frequency of contacts varies from daily to monthly. According to the participants, it is very good to see friends from their home country, with the most common shared activities being eating or going to restaurants, drinking or going to bars and staying at home. Both old (compatriots) and new friends (usually natives of the new country or other immigrants) are important in the process of migration from one culture to another. The beginning of friendships in the new country happens, for the most part, in the academic environment, through other friends and through relatives. Finally, Latin American immigrants in Brazil and Brazilians in other Latin American countries demonstrated a mostly positive view of natives before establishing friendships with them; and Brazilian immigrants in Spain and Portugal a negative view. DOI:https://doi.org/10.56238/sevened2024.026-058